Inheritance of resistance to Kabatielle eyespot of maize - Chang, M.S.; Hudon, M.; Devaux, A. (Phytoprotection, 1990)
Genetic studies of resistance to Kabatiella zeae causing eyespot in grain maize (Zea mays) were conducted using an 8 x 8 complete diallel cross. In the eight inbreds used, the additive component appeared to be the most important in determining resistance to eyespot. There appeared to be at least four genes showing some degree of dominance. Narrow-sense heritability was estimated at 75%. Inbred V312 was the most resistant line among the eight lines in this diallel set, whereas F522, WF9 and L2039 appeared to be susceptible.